Primary thymic mucosa-associated lymphoid tissue lymphoma complicated with renal amyloidosis: A first case report. Issue 13 (March 2020) - Chen, Qin; Du, Yongjing; Prince, Singh; Zhang, Ping; Li, Guisen; Wang, Li; Wang, Wei
Abstract: Introduction: Primary mucosa-associated lymphoid tissue (MALT) lymphomas originating in thymus is rare. And, there have been few reports of patients with MALT coexisting with amyloidosis. As far as we know, this was the first case report on MALT lymphoma associated with renal amyloidosis. Patient concerns: A 57-year-old man presented with nephrotic syndrome. Further workup revealed IgM-Lambda type monoclonal gammopathy. Bone marrow biopsy showed 8% clonal plasma cells. Renal biopsy confirmed the diagnosis of Lambda light chain AL amyloidosis. positron emission tomography/computed tomography showed thymic lesions which upon biopsy were diagnosed as MALT lymphoma of the thymus. Diagnosis: Primary thymic MALT lymphoma complicated with renal amyloidosis. Interventions: The patient underwent surgical resection of the thymus mass and 2 courses of chemotherapy. Outcomes: Follow-up data showed that the patient survived 18 months after surgical excision and chemotherapy. Conclusion: The case highlights the importance of screening for malignancy in patients with renal amyloidosis.